Determination and Occurrence of Mineralocorticoids in Taihu Lake of China - Zhao, Li; Chang, Hong; Sun, Fuhong; Su, Hailei (Frontiers in Environmental Science, 2021)
We developed a sensitive method for monitoring six natural (aldosterone) and synthetic mineralocorticoids (canrenone, spironolactone, 7β-spironolactone, 7α-thio spironolactone, and 7α-thiomethyl spironolactone) in sediment and water using ultra-performance liquid chromatography–electrospray tandem mass spectrometry, and then 30 water and 30 sediment samples were analyzed to reveal their occurrence and distributions in Taihu Lake. All target six mineralocorticoids were detected in sediment and water samples with the detection frequencies as high as 96-100%. The median concentrations of mineralocorticoids ranged from 0.04 ng/L (7α-thiomethyl spironolactone) to 14 ng/L (aldosterone) in water and 0.01 ng/g (7β-spironolactone and canrenone) to 1.44 ng/g (aldosterone) in sediment in dry weight. Natural aldosterone was the predominant mineralocorticoid detected in both water and sediment samples, indicating the mineralocorticoid pollution in Taihu Lake was mainly derived from human and/or animal excrement rather than pharmaceutical industry and usage. Two metabolites 7β-spironolactone and 7α-thio spironolactone were first found in this study. Low ratios of metabolites to spironolactone were observed in sediment (0.05-0.75) in contrast to water (0.12-2.26), indicating that spironolactone was prone to degradation in water phase compared to sediment environment.